2015
DOI: 10.7314/apjcp.2015.16.15.6365
|View full text |Cite
|
Sign up to set email alerts
|

Women and Tobacco Use: Discrepancy in the Knowledge, Belief and Behavior towards Tobacco Consumption among Urban and Rural Women in Chhattisgarh, Central India

Abstract: Background: Tobacco consumption has become pandemic, and is estimated to have killed 100 million people in the 20th century worldwide. Some 700,000 out of 5.4 million deaths due to tobacco use were from India. The era of global modernization has led to an increase in the involvement of women in tobacco consumption in the low income and middle-income countries. Tobacco consumption by females is known to have grave consequences. Objectives: To assess: (1) the tobacco use among urban and rural women; (2) the disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Smoking behaviours were gendered from the outset: nearly all smokers were male at the beginning of 20th century. However, alongside economic and social development, the prevalence of female smokers increased in many countries 4 5. Moreover, the age at which people begin smoking has dropped lower over the last century in Asian countries like China 6.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking behaviours were gendered from the outset: nearly all smokers were male at the beginning of 20th century. However, alongside economic and social development, the prevalence of female smokers increased in many countries 4 5. Moreover, the age at which people begin smoking has dropped lower over the last century in Asian countries like China 6.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the findings of another study done in central India among the women residing in both the rural and urban areas, the prevalence was 54.4%. [ 17 ] Further, it was reported that the prevalence of tobacco consumption among women was quite common in a rural area than in an urban area. [ 17 ] This could be due to the lack of awareness activities and poor sensitization of the general population, including women.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of migrant labourers was assessed using a structured knowledge questionnaire prepared by the investigators after ensuring the validity and reliability. The questionnaire included items regarding to tobacco products, and health hazards due to tobacco usage and data [5][6][7][8][9][10] was collected through interview technique. The researchers also collected data on demographic details of the samples and habits of tobacco and pan chewing through structured tool and interviewing the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers also collected data on demographic details of the samples and habits of tobacco and pan chewing through structured tool and interviewing the samples. A video including introduction to tobacco and pan chewing, ill effects of tobacco and pan chewing, ways to avoid tobacco and pan chewing habits was prepared by the researchers and validated by [5][6][7][8][9][10] experts from different disciplines. The study was completed within 9 months.…”
Section: Methodsmentioning
confidence: 99%